Pengaruh Kunjungan Perusahaan terhadap Pengetahuan Akademik Mahasiswa dengan Relevansi Materi sebagai Mediator - Rini Kurnia Sari; Aisyah Qanita; Made Irma Lestari (Universitas Muhammadiyah Ponorogo, 2026)
This study investigates the effect of company visit activities on students’ academic knowledge, with material relevance as a mediating variable. Grounded in experiential learning theory, the research explores how real-world industrial exposure enhances students’ conceptual understanding. Data was collected through a structured questionnaire from 41 students at a private university in Jakarta who participated in a company visit to CRSN, representing diverse academic programs. The analysis employed Structural Equation Modeling (SEM) using SmartPLS to assess both measurement and structural models. The outer model evaluation confirmed good reliability and validity of all constructs. The results reveal that company visit activities have a significant and positive direct effect on students’ academic knowledge and significantly influence their perception of material relevance. However, material relevance does not have a significant direct effect on academic knowledge and does not mediate the relationship between company visit activities and academic knowledge. These findings suggest that while students acknowledge the value of relevant material during visits, direct experiential exposure remains the primary driver of knowledge development. The study contributes to the literature by highlighting the importance of integrating industry-based learning in higher education. It also suggests that company visits should be followed by reflective or structured academic activities to maximize their educational impact.